Experimental use of an acrolein-based primer as collagen cross-linker for dentine bonding. (January 2018) - Maravic, Tatjana; Breschi, Lorenzo; Comba, Allegra; Cunha, Sandra Ribeiro; Angeloni, Valeria; Nucci, Cesare; Hebling, Josimeri; Pashley, David; Tay, Franklin; Mazzoni, Annalisa
Abstract: Objectives: The objective of the present study was to investigate the long-term effect of 0.01% acrolein (ACR) aqueous solution, employed as an additional primer, on the mechanical durability and enzymatic activity of resin-dentine interfaces created with a simplified etch-and-rinse adhesive. Methods: Dentine surfaces were etched with 35% phosphoric acid for 15 s, rinsed and blot-dried. Specimens were then assigned to: Group 1: dentine pre-treated with 0.01% ACR aqueous solution for 1 min and bonded with Adper Scotchbond 1 XT (SB1XT), a 2-step etch-and-rinse adhesive; Group 2: SB1XT was applied on untreated acid-etched dentine (control). Resin composite build-ups were made using Filtek Z250. Microtensile bond strength was tested by stressing sectioned specimens to failure immediately or after 1 year of storage in artificial saliva at 37 °C. Zymography and in-situ zymography assays were performed for examining dentine matrix metalloproteinase (MMP) activities. Results: The use of 0.01% ACR as conditioning primer appeared to have contributed better to preservation of bond strength over time without affecting immediate bond strength. Zymography and in-situ zymography showed reduction in MMP activities after the application of ACR. Conclusion: Dentine collagen cross-linking produced by an ACR-based primer increases the longevity of resin-dentine bonds by reinforcement of the adhesive interface and reduction of dentine MMP activities. Further studies are required to evaluate the potential in vivo and in vivo cytotoxicity of ACR. Clinical significance: The acrolein-based primer is a potentially useful clinical bonding tool because it demonstrates good collagen cross-linking ability within a clinically-acceptable working time. Although a low ACR concentration was employed in the present study, the cytotoxicity of ACR should be tested prior to clinical use.